Teaching Othering In Education Using “X-MEN” Movie - Susanto Susanto; Dwi Ario Fajar (JELLE : Journal Of English Literature, Linguistics, and Education, 2020)
Teaching abstract concept in literature like othering to English students can be challenging for it is difficult for students to visualize and relate to their reality. Using popular movie can help them visualize the concept lively. Popular science fiction movie like X-Men is not merely imaginative and full of fantasy; it also has relevant issue on concept of othering in Education. Therefore, instead of using it as means of teaching English skill, it can also be used as mean of helping students easily to understand difficult and abstract concept especially about othering in education. Deconstruction method and theory of movie for ELT is explored to describe othering in X-Men movie and how to the use of X-Men film as the mean to teach othering in education.It is found that X-Men provided critics of othering in education represented by negative views and different treatments to mutantsin field of education. The practices of othering were in form of discourses like seeing mutants as abnormal, a threat to normal people, and diseases needed curing and they were not allowed to go to normal school. To present the othering concept in X-Men, the lesson session were divided into three parts; previewing, viewing and post viewing.Keywords: X-Men, movie for ELT, othering in education